Elevated plasma concentrations of homocysteine in antiepileptic drug treatment - Schwaninger, Markus; Ringleb, Peter A.; Winter, Ralph; Kohl, Brigitte; Fiehn, Walter; Rieser, Peter A.; Walter-Sack, Ingeborg (Epilepsia, 1999)
Summary: Purpose: Homocysteine is an experimental convulsant and an established risk factor in atherosclerosis. A nuritional deficiency of vitamin B6, vitamin B12, or folate leads to increased homocysteine plasma concentrations. During treatment with carbamazepine (CBZ), phenytoin, or phenobarbital, a deficiency in these vitamins is common. The objective of the study was to test the hypothesis that antiepileptic drug (AED) treatment is associated with increased homocysteine plasma concentrations. Methods: A total of 51 consecutive outpatients of our epilepsy clinic receiving stable, individually adjusted AED treatment and 51 sex- and age-matched controls were enrolled in the study. Concentrations of total homocysteine and vitamin B6 were measured in plasma; vitamin B12 and folate were measured in the serum of fasted subjects. Results: Patients and controls differed significantly in concentrations of folate (13.5 ± 1.0 vs. 17.4 ± 0.8 nM and vitamin B6 (39.7 ± 3.4 vs. 66.2 ± 7.5 nM), whereas serum concentrations of vitamin B12 were similar. The homocysteine plasma concentration was significantly increased to 14.7 ± 3.0 μM in patients compared with controls (9.5 ± 0.5 μM; p < 0.05, Wilcoxon rank-sum test). The number of patients with concentrations of >15 μM was significantly higher in the patient group than among controls. The same result was obtained if only patients with CBZ monotherapy were included. Patients with increased homocysteine plasma concentrations had lower folate concentrations. Conclusions: These data support the hypothesis that prolonged AED treatment may increase plasma concentrations of homocysteine, although the alternative explanation that increased homocysteine plasma concentrations are associated with the disease and not the treatment cannot be completely excluded at the moment.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 01.04.2021